Downregulation of β1 Integrins by Ebola Virus Glycoprotein: Implication for Virus Entry - Takada, Ayato; Watanabe, Shinji; Ito, Hiroshi; Okazaki, Katsunori; Kida, Hiroshi; Kawaoka, Yoshihiro (Virology (New York, N.Y.), 2000)
Filoviruses, including Ebola virus, are cytotoxic. To investigate the role of the Ebola virus glycoprotein (GP) in this cytopathic effect, we transiently expressed the GP in human kidney 293T cells. Expression of wild-type GP, but not the secretory form of the molecule lacking a membrane anchor, induced rounding and detachment of the cells, as did a chimeric GP containing its ectodomain and influenza virus hemagglutinin transmembrane–cytoplasmic domain. These results indicate that the GP ectodomain and its anchorage to the membrane are required for GP-induced morphologic changes in host cells. Since cell rounding and detachment could be associated with reduced levels of cell adhesion molecules, we also studied the expression of integrins, which are major molecules for adhesion to extracellular matrices, and found that the β1 integrin group is downregulated by the GP. This result was further extended by experiments in which anti-β1 monoclonal antibodies or purified integrins inhibited the infectivity of vesicular stomatitis virus pseudotyped with the GP. We suggest that integrins, especially the β1 group, might interact with the GP and perhaps be involved in Ebola virus entry into cells.